Control of Fusarium Wilt of Tomato Caused by Fusarium oxysporum F. Sp. Radicis-Lycopersici Using Mixture of Vegetable and Posidonia oceanica Compost - S. Kouki; N. Saidi; A. Ben Rajeb; M. Brahmi; A. Bellila; M. Fumio; A. Hefiène; N. Jedidi; J. Downer; H. Ouzari (Applied and Environmental Soil Science)
A compost of vegetable waste and Posidonia oceanica mixture (70 : 30% vol : vol) was tested in vitro and in vivo for its efficacy against Fusarium oxysporum f.sp radicis-lycopersici (Forl), the causal agent of Fusarium wilt of Tomato (Lycopersicon esculentum cv. chourouk).The incorporation of non-sterilized VPC in the culture medium showed potent antifungal activity against Forl and complete inhibition of mycelium growth was observed for all the tested compost rates (0.5, 1, 2, 4, 6, 8, 10, 15 and 20%). However, only the highest rates (15 and 20%) of a sterilized suspension of VPC were effective in preventing mycelial growth. Nine indigenous bacterial strains isolated from VPC exhibited antagonism against Forl. Based on 16S rDNA sequence analysis, the isolates were assigned to Bacillus sphaericus (B12 and BS2), Pseudomonas putida PPS7 and Burkholderia gladioli BuC16. Under green house condition, seed inoculation by B12, BS2, PP7 and BuC16 strains protected significantly tomato against Fusarium oxysporum f.sp radicis-lycopersici (Forl) attacks.